Етнографія Словаччини у період національного відродження - Леньо, П. (Народна творчість та етнографія, 2005)
This article is an overlook of the Slovak ethnography from the first ethnographical knowledge of the 18th Century to the creation of the ethnography as a scholarly discipline and then Slovak ethnography in the 19th Century. The author is mentioning the fact that Slovak ethnography never been in the status of Chech Ethnography for instance but succeeded to create some great scholars and ideas. Main goal of Slovak ethnography of the 19th Century was to found proves of the ethnical individuality of Slovaks in order to prevent them from assimilation.